Novel trial designs: Master protocol trials - Priya Ranganathan; Vishal Deo; C. S. Pramesh; Mahesh P. Parmar (Perspectives in Clinical Research)
Conventional trial designs are resource and time-intensive. To accelerate the process of testing new interventions, we now have several novel research trial designs. This article focuses on master protocol trials, which allow several therapies to be tested within a single larger trial.